MEDICAL AND DIETARY MANAGEMENT STRATEGIES FOR CANINE NEPHRITIS - Aricahyani, Ni Luh; Jayanti, Putu Devi; Erawan, I Gusti Made Krisna (Buletin Veteriner Udayana, 2025)
Canine nephritis, an inflammatory kidney condition, progressively impairs renal function through glomerular and interstitial damage. This case report documents a dog presenting with dysuria, hematuria, and yellow foamy vomiting, accompanied by anorexia with partial maintenance of water intake. The patient had a long-term dietary history of rice, chicken breast, and inappropriate high-protein commercial snacks/supplements since puppyhood. Diagnostic evaluation revealed marked azotemia (BUN >45.00 mmol/L, creatinine 168.7 μmol/L), hyperproteinemia (90.9 g/L), and ultrasonographic evidence of cortical thickening. A comprehensive treatment protocol was implemented: (1) 72-hour intravenous Ringer's lactate fluid therapy, (2) transition to renal-support wet food (Royal Canin® Renal Support) twice daily, and (3) daily Ipakitine® (Vetoquinol) supplementation for 14 days. Therapeutic outcomes demonstrated significant biochemical improvement (BUN 14.12 mmol/L, creatinine 63.4 μmol/L) and complete resolution of clinical signs. This case highlights the importance of combined fluid therapy, dietary modification, and phosphate-binding management in canine nephritis cases with nutritional etiology.